Apelin-APJ Signaling: a Potential Therapeutic Target for Pulmonary Arterial Hypertension - Kim, Jongmin (Korean Society for Molecular and Cellular Biology, 2014)
Pulmonary arterial hypertension (PAH) is a progressive disease characterized by the vascular remodeling of the pulmonary arterioles, including formation of plexiform and concentric lesions comprised of proliferative vascular cells. Clinically, PAH leads to increased pulmonary arterial pressure and subsequent right ventricular failure. Existing therapies have improved the outcome but mortality still remains exceedingly high. There is emerging evidence that the seven-transmembrane G-protein coupled receptor APJ and its cognate endogenous ligand apelin are important in the maintenance of pulmonary vascular homeostasis through the targeting of critical mediators, such as Krűppel-like factor 2 (KLF2), endothelial nitric oxide synthase (eNOS), and microRNAs (miRNAs). Disruption of this pathway plays a major part in the pathogenesis of PAH. Given its role in the maintenance of pulmonary vascular homeostasis, the apelin-APJ pathway is a potential target for PAH therapy. This review highlights the current state in the understanding of the apelin-APJ axis related to PAH and discusses the therapeutic potential of this signaling pathway as a novel paradigm of PAH therapy.